Plastics processing data handbook - Rosato, Dominick V. (Chapman & Hall, 1997)
This comprehensive workbook offers a thorough review of today's high performance plastics and manufacturing processes. Focusing on common processing problems and practical solutions this book surveys fundamental processing concepts for every major fabrication technique in use today and provides extensive data on controls, instrumentation, materials and molding technologies. This second edition is fully updated with the addition of new material, new tables and new figures.